Standardized Patient Modules in Medical School with the Lesbian, Gay, Bisexual & Transgender Patient in Mind - Anderson, OMS IV, Jacob; Stoner, PhD, MPH, Alexis M.; Jackson, MSc, Ashley; Januchowski, DO, Ronald; Myles, DO, Darlene (Osteopathic Family Physician, 2018)
Objective: This study was designed with the intent to serve as an exploratory pilot and first step toward integrating Lesbian, Gay, Bisexual, and Transgender (LGBT) clinical education into the curriculum of Osteopathic and southeastern medical schools. Methods: Using a quasi-experimental study, second year Osteopathic medical students were studied for their clinical knowledge of LGBT health, attitudes toward LGBT patients, and use of sensitive language while obtaining sexual history from Standardized Patients (SPs) before and after exposure to a didactic module. Results: We found attitudes of LGBT health to be unaffected by the intervention (P=0.63) while clinical knowledge improved (P=0.11). Sensitive language used by students during sexual history gathering was similar between groups with no correlation with student LGBT health/knowledge scores. The results support previous literature suggesting a change in medical school curriculum can increase student awareness of LGBT health needs. Attitude scores toward LGBT patients of the studied students were slightly lower than those of six other osteopathic schools, and within the constraints of this study it appears a single didactic module was insufficient in changing attitude scores. Conclusion: With research being limited on this topic, our study provides guidance and methods for implementing LGBT care training into Osteopathic medical education. We hope our baseline data in conjunction with other studies will provoke further research into the most effective means for implementation. Further research should include multi-modal didactics including small group sessions, lectures, and clinical exposure to LGBT individual(s), as has been suggested and implemented in few other studies.